Kajian Literatur: Peran Penalaran Matematis dalam Pengembangan Kompetensi Matematika Siswa SMP - Syafa'atun (JPT : Jurnal Pendidikan Tematik, 2024)
This literature review aims to analyze the role of mathematical reasoning in developing junior high school students' mathematical competence. Mathematical reasoning is a very important cognitive skill to help students understand mathematical concepts, solve problems, and develop critical thinking skills. Based on studies from various previous studies, it was found that various factors, such as active learning approaches, the use of technology, and teacher support, play a significant role in improving students' mathematical reasoning abilities. In addition, problem-based learning, constructivist approaches, and the integration of technology in learning have been proven to encourage students to be more active and creative in solving mathematical problems. This study also revealed that developing students' learning motivation and strengthening the relationship between students and teachers can strengthen the mathematical reasoning process. Thus, this study provides important insights into the importance of these factors in developing students' mathematical competence at the junior high school level.